Respuesta :

Answer:

Step-by-step explanation:

Step 1: Equation at the end of step 1

Simplifying

60(x + 20) = 3x

Reorder the terms:

60(20 + x) = 3x

(20 * 60 + x * 60) = 3x

(1200 + 60x) = 3x

Solving

1200 + 60x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

1200 + 60x + -3x = 3x + -3x

Combine like terms: 60x + -3x = 57x

1200 + 57x = 3x + -3x

Combine like terms: 3x + -3x = 0

1200 + 57x = 0

Add '-1200' to each side of the equation.

1200 + -1200 + 57x = 0 + -1200

Combine like terms: 1200 + -1200 = 0

0 + 57x = 0 + -1200

57x = 0 + -1200

Combine like terms: 0 + -1200 = -1200

57x = -1200

Divide each side by '57'.

x = -21.05263158

Simplifying

x = -21.05263158

ACCESS MORE